Competition of fintech companies against commercial banks: a threat or an opportunity? - Mukhiddinova Iroda Farkhod kyzy,,; Akhmedova Firuza Abdumajidovna, (THE INNOVATION ECONOMY, 2026)
This article analyzes the competition of fintech companies against commercial banks. As a result of the development of modern financial and digital technologies, fintech companies are creating a new competitive environment for banks. This competition can be seen as a threat to banks, as fintech companies offer fast, affordable convenient and innovative services. However, this competition can also be an opportunity for banks. They are trying to develop new strategies to digitize their activities and improve the quality of services. The article examines the positive and negative aspects of competition between commercial banks and fintech companies, as well as the prospects for their cooperation